Are Social Indifference Curves Convex? - Gorman, W. M. (Quarterly Journal of Economics, 1959)
Introduction, 485. — Samuelson's postulate on social indifference curves, 486. — Importance to it of the concept of diminishing marginal rates of substitution, 486. — Assumption that it reflects the prevaijing egalitarian ethic and the concept of ' diminishing marginal utility, 487. — In fact it has little to do with “egalitarianism” and is much more closely related to “moderation,” 489. — Model showing Samuelson's postulate and some of the cases in which it may not hold, 489. — The problem of convexity and the relationship between “social” and “community” indifference curves, 495.